A two-enzyme cascade reaction consisting of two reaction pathways. Studies in bulk solution for understanding the performance of a flow-through device with immobilised enzymes. Issue 32 (18th May 2020) - Ghéczy, Nicolas; Sasaki, Kai; Yoshimoto, Makoto; Pour-Esmaeil, Sajad; Kröger, Martin; Stano, Pasquale; Walde, Peter
Abstract : A cascade reaction catalysed by bovine carbonic anhydrase (BCA) and horseradish peroxidase (HRP) proceeds over two possible pathways, which explains differences in product formation for differently immobilised enzymes in flow-through reactions. Abstract : Enzyme-catalysed cascade reactions in flow-through systems with immobilised enzymes currently are of great interest for exploring their potential for biosynthetic and bioanalytical applications. Basic studies in this field often aim at understanding the stability of the immobilised enzymes and their catalytic performance, for example, in terms of yield of a desired reaction product, analyte detection limit, enzyme stability or reaction reproducibility. In the work presented, a cascade reaction involving the two enzymes bovine carbonic anhydrase (BCA) and horseradish peroxidase (HRP) – with hydrogen peroxide (H2 O2 ) as HRP "activator" – was first investigated in great detail in bulk solution at pH = 7.2. The reaction studied is the hydrolysis and oxidation of 2′, 7′-dichlorodihydrofluorescein diacetate (DCFH2 -DA ) to 2′, 7′-dichlorofluorescein (DCF ), which was found to proceed along two reaction pathways. This two-enzyme cascade reaction was then applied for analysing the performance of BCA and HRP immobilised in glass fiber filters which were placed inside a filter holder device through which a DCFH2 -DA /H2 O2 substrate solution was pumped. Comparison was made between (i) co-immobilised and (ii) sequentially immobilised enzymes (BCA first, HRP second). Significant differences for the two arrangements in terms of measured product yield (DCF ) could be explained based on quantitative UV/vis absorption measurements carried out in bulk solution. We found that the lower DCF yield observed for sequentially immobilised enzymes originates from a change in one of the two possible reaction pathways due to enzyme separation, which was not the case for enzymes that were co-immobilised (or simultaneously present in the bulk solution experiments). The higher DCF yield observed for co-immobilised enzymes did not originate from a molecular proximity effect (no increased oxidation compared to sequential immobilisation).